Schizofrenia, imputabilità e infermità mentale - Fargnoli, Domenico (Il sogno della farfalla, 2014)
The author retraces the contrast between two alternative models of approach to mental health: the “punitive moralistic approach” typical of the magistrature and the “empathic therapeutic approach” typical of psychiatry. In fact, the punitive moralistic model, in spite of developments in modern psychiatry, is by far the prevalent one both in terms of the social practice of the internment of mental patients in prisons and ideology. The legal concept of “infirmity” is functional to the negation of mental illness and a nosography founded on psychopathological criteria. The author reinterprets a famous case of infanticide which happened in Cogne (Italy) in 2001 in light of the most recent research into the psychopathology of schizophrenia and into delirious perception made possible by M. Fagioli’s theory. New interpretations of this kind could have important repercussions on forensic psychiatry.